Awareness of female college students about the values ​​of citizenship in Islamic educational thought and the role of colleges of education in strengthening them - Mezuo, Manal Ammar (Journal of Educational and Psychological Sciences, 2020)
The study aims at identifying the awareness of female college students about the values ​​of citizenship in Islamic educational thought and the role of colleges of education in strengthening them, The study used the descriptive approach, and the study sample included a random size of (500) female students by 100 students from each university, and the study tool included four axes, the first axis dealt with the awareness of the value of Arab-Islamic culture, and the second axis dealt with the awareness of the importance of the Arabic language, and the third axis dealt with Awareness of the importance of religious events. The fourth axis dealt with the role of colleges of education, as well as relying on arithmetic averages in addition to analyzing multiple variances. All statistical treatments were done using the SPSS (v12) statistical program. The results of the field study showed that the students are very aware of the values ​​of citizenship as well as the role of the colleges of education, as all the averages approached the great end for each dimension, and the results also showed there are no statistically significant differences in the level of students’ awareness of the values ​​of citizenship and the role of colleges of education depending on the variables of the university and the division and interaction between them. In light of the results, the study made some recommendations, including that student activities must be characterized by diversity, with the participation of the largest possible number of students, the curricula should include in their content the values ​​of citizenship, such as collective spirit and commitment to the standards and regulations of society, the students’ curricula should develop the principle of freedom of expression and the culture of dialogue, the university professor’s behavior must match his ideas in educational situations and the necessity of conducting similar studies on other samples such as graduate students and female students in pre-university education stages.